The contribution of philosophy of science to the development of islamic education management science - Baijuri (12 Waiheru, 2025)
This article explores the contribution of the philosophy of science in the development of Islamic education management through a qualitative approach and literature analysis. The literature sources used come from various journals, books, and relevant academic documents, with selections that consider credibility and relevance to the topic. Although it does not use the Systematic Literature Review (SLR) method or meta-analysis, this study includes sufficient references to support its argument. The main findings show that the philosophy of science contributes to three important aspects. First, the philosophy of science built a systematic framework of thinking that allows the management of Islamic education to be carried out in a more planned and effective manner. Second, Islamic values are integrated with modern management theory, resulting in an efficient and ethical management model. Third, the philosophy of science provides a moral basis in education management, emphasizing the importance of values such as justice and responsibility in decision-making. Thus, the philosophy of science is very significant in answering the challenges of Islamic educational institutions in the contemporary era and strengthening the commitment to the moral values that underlie Islamic education.